2020
DOI: 10.1371/journal.pone.0223393
|View full text |Cite
|
Sign up to set email alerts
|

Micronutrient intake and prevalence of micronutrient inadequacy among women (15-49 y) and children (6-59 mo) in South Kivu and Kongo Central, Democratic Republic of the Congo (DRC)

Abstract: Iron biofortified beans and carotenoid enriched cassava are proposed as a solution to combat iron and vitamin A deficiencies, respectively, in the Democratic Republic of Congo (DRC). To inform the need for biofortified foods, we conducted a survey in 2014 in two provinces of the DRC, South Kivu and Kongo Central. Unexpectedly, women of reproductive age (WRA; 15-49 y) and their children (6-59 m) had a low prevalence of biochemical iron and vitamin A deficiency, based on ferritin and retinol binding protein, res… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 17 publications
1
8
0
Order By: Relevance
“…The intake of daily dietary iron by the women in LMICs (3.8–36.0 mg) was above the daily EAR of 15 mg. The studies in Ethiopia (36.0 mg) (Asayehu et al., 2017 ), Vietnam (15.5 mg) (Nguyen et al., 2014 ), Congo (18.8–20.3 mg) (Moumin et al., 2020 ), Nigeria (16.8 mg) (De Moura et al., 2015 ), and India (22.3 mg) (Loukrakpam et al., 2020 ) indicated that dietary iron intake was satisfactory compared to the EAR. On the other hand, studies in Lebanon (8.0 mg) (Abou‐Rizk et al., 2021 ), India (7.39 mg) (Nunn et al., 2019 ), Zambia (7.39 mg) (Kaliwile et al., 2019 ), and South Africa (3.8 mg) (Oldewage‐Theron & Kruger, 2011 ), and Bangladesh (6.72–11.63 mg) (Akter et al., 2021 ; Arsenault et al., 2013 ; M. H. Islam et al., 2021 ; Sultana et al., 2019 ) showed lower intake of iron than the recommended EAR.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The intake of daily dietary iron by the women in LMICs (3.8–36.0 mg) was above the daily EAR of 15 mg. The studies in Ethiopia (36.0 mg) (Asayehu et al., 2017 ), Vietnam (15.5 mg) (Nguyen et al., 2014 ), Congo (18.8–20.3 mg) (Moumin et al., 2020 ), Nigeria (16.8 mg) (De Moura et al., 2015 ), and India (22.3 mg) (Loukrakpam et al., 2020 ) indicated that dietary iron intake was satisfactory compared to the EAR. On the other hand, studies in Lebanon (8.0 mg) (Abou‐Rizk et al., 2021 ), India (7.39 mg) (Nunn et al., 2019 ), Zambia (7.39 mg) (Kaliwile et al., 2019 ), and South Africa (3.8 mg) (Oldewage‐Theron & Kruger, 2011 ), and Bangladesh (6.72–11.63 mg) (Akter et al., 2021 ; Arsenault et al., 2013 ; M. H. Islam et al., 2021 ; Sultana et al., 2019 ) showed lower intake of iron than the recommended EAR.…”
Section: Resultsmentioning
confidence: 99%
“…Per day intake of vitamin A by WRA in LMICs was 63.61–2441 μg. Although the consumption of vitamin A was inadequate in most of the studies as compared to the EAR (390 μg), the studies in Vietnam (783 μg) (Nguyen et al., 2014 ), Congo (757–1109 μg) (Moumin et al., 2020 ), Ethiopia (2037.9 μg) (Asayehu et al., 2017 ), and Nigeria (2441 μg) (De Moura et al., 2015 ) showed adequate intake of vitamin A among the WRA.…”
Section: Resultsmentioning
confidence: 99%
“…The serum was collected from 412 children aged 1–5 years. The boy/girl ratio was 1:1, and their median (P25–P75) age was 32 [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ] months. Table 1 shows the general characteristics of the children included in this study.…”
Section: Resultsmentioning
confidence: 99%
“…However, our observations in Popokabaka (Kwango Province) seem to be more severe than the ones from the Kongo Central and south Kivu provinces in DRC (25–29%), as reported by Harvey-Leeson in 2016 [ 21 ]. This remarkable difference could be explained by the difference in dietary habits and the better food availability and diversity observed in the Kongo Central and south Kivu regions than in Popokabaka [ 32 ]. For instance, communities in the Kivu province are pastoral, commonly practice livestock, and have great accessibility to meat, beans, and potatoes, which are culturally accepted as staple foods.…”
Section: Discussionmentioning
confidence: 99%
“…In South Kivu, studies reported an anemia prevalence of 16.5–17.6% in pregnant and non-pregnant women of reproductive age (DHS: 22.7%) and 47.8–58.6% in children aged 6–23 months (DHS: 35.7% in children 6–59 months) [ 8 , 9 , 10 , 11 ]. Also, in South Kivu, Moumin et al [ 12 ] found a moderate prevalence of inadequate vitamin A (18%) and iron intake (33%) among women of reproductive age, and moderate to high inadequacy of further nutrients such as folate or zinc. Despite this evidence on poor diet in the region, to our knowledge, evidence on the determinants of dietary practices such as nutritional knowledge and attitudes, and their potential relationship with anemia status is scarce, especially for lactating women.…”
Section: Introductionmentioning
confidence: 99%